2010
DOI: 10.1007/s10593-010-0497-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of n-aminoglycosides derived from alkaloid cytisine, their biological activity and crystal structure of N-(β-D-galactopyranosyl)cytisine

Abstract: Optimal conditions were found for the synthesis of a number of new N-aminoglycosides of the alkaloid cytisine, using commercially available monosaccharides, namely, D-glucose, D-galactose, D-xylose, and L-arabinose. X-ray structural analysis indicated an absolute -anomeric configuration of N-(-D-galactopyranosyl)cytisine in the crystalline state. The comparative cytotoxicity of cytisine and some of its N-aminoglycosides was determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Interestingly, compounds 1 – 4 possessed three undescribed dimerization patterns containing cytisine, while compounds 5 and 6 represented the first example of addition products of cytisine and 5,6-dihydroxy-4-hexanolide (Figure ). In addition, compound 7 was identified as N -(β- d -glucopyranosyl)­cytisine . Further biological studies showed that some compounds exhibited strong anti-tobacco mosaic virus (TMV) activities.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, compounds 1 – 4 possessed three undescribed dimerization patterns containing cytisine, while compounds 5 and 6 represented the first example of addition products of cytisine and 5,6-dihydroxy-4-hexanolide (Figure ). In addition, compound 7 was identified as N -(β- d -glucopyranosyl)­cytisine . Further biological studies showed that some compounds exhibited strong anti-tobacco mosaic virus (TMV) activities.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of a new fused heterocyclic ring is an important task for heterocyclic chemistry from various points of view. The reactions of thiazolo[3,2‐ a ]pyrimidines have attracted the attention of many chemists and used them in the synthesis of different heterocycles [1–15] possessing biological [10–14] and medicinal activities [15]. These observations in continuation with our general interest in these compounds led us to examine the chemistry of pyrazolinyl thiazolopyrimidine carboxylate to be used as starting material for the synthesis of novel thiazolopyrimidines and thiazolopyrimidopyrimidines bearing pyrazolone moiety, which have biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, compounds with types of biological activity that are uncharacteristic of cytisine itself are constantly being discovered. Until now many cytisine derivatives with various heterocylic groups such as coumarin [2,3]; 1,2,3-triazole [4]; 1,2,4-thiadiazole [5]; 1,3-thiazoline [6]; 2,5-dimercapto-1,3,4-thiadiazole [7]; barbituric acid [8]; pyridine [9]; 1,4-dihydropyridine [10]; and phenothiazine [11] were prepared.The Mannich reaction, which is widely used in organic chemistry to synthesize a variety of practically important compounds, is a convenient method for preparing new N-derivatives of cytisine in addition to the broadly used nucleophilic substitution and addition reactions of cytisine [2][3][4][5][6][7][9][10][11].The starting synthons for preparing new N-heterocyclic cytisine derivatives were 3,4-dihydropyrimidin-(1H)-2-thione derivatives, which were obtained via three-component condensation using a Biginelli reaction. The number of publications on the chemistry of 4-aryl-3,4-dihydropyrimidin-2-ones and 4-aryl-3,4-dihydropyrimidin-2-thiones has recently increased significantly in the scientific literature.…”
mentioning
confidence: 99%
“…The Mannich reaction, which is widely used in organic chemistry to synthesize a variety of practically important compounds, is a convenient method for preparing new N-derivatives of cytisine in addition to the broadly used nucleophilic substitution and addition reactions of cytisine [2][3][4][5][6][7][9][10][11].…”
mentioning
confidence: 99%
See 1 more Smart Citation